Evaluation of cold ironing and speed reduction policies to reduce ship emissions near and at ports - Zis, Thalis; North, Robin; Angeloudis, Panagiotis; Ochieng, Washington Yotto; Bell, Michael G. H. (My University, 2014)
Alternative port operating policies have the potential to reduce pollutant emissions from shipping; however their efficacy is expected to vary from port to port. This paper extends existing literature to present a consistent and transferable methodology for the consideration of such policies for any port based on ship-call data. Emissions of carbon dioxide (CO2); sulphur dioxide (SO2); nitrogen oxides (NOx); and black carbon (BC) are estimated from near-port container ship activities, including consideration of the associated fuel costs. The method is implemented for a set of typical container terminal types and two common emissions reduction policies. Results show that full compliance of all calling vessels with a speed reduction scheme can lead to reductions of 8-20%, 9-40%, and 9-17% for CO2, SO2, and NOx respectively. In contrast, for BC, speed reduction policies may increase emissions up to 10%. In both cases these changes are critically dependent on the baseline operating pattern of the ships. For the same terminals, provision of Alternative Marine Power (AMP) for all berthing vessels can lead to reductions of in-port emissions of 48-70%, 3-60%, 40-60%, and 57-70% for CO2, SO2, NOx and BC respectively. These benefits rely on suitable equipment being carried by vessels, with large benefits associated with larger vessels. This analysis serves to highlight that emissions are critically dependent on the visiting fleet, berthing durations, sulphur reduction policies in force and the emissions intensity of the port electricity supply. For both speed-reduction schemes and AMP, increased total emissions are possible, making it essential to evaluate and prioritize alternative port operating policies for emissions reduction based on the characteristics of individual ports.
Keywords: Port Policy; Maritime transportation; Ship emissions; Slow steaming; Cold ironing